(Re)remembering and narrating the childhood city of R.D. Laing. (July 2013) - McGeachan, Cheryl
In recent years, geographical engagements with issues surrounding different forms of memory have become increasingly diverse. Responding to Owain Jones's recent call for more attention to be paid in geography to the individual and private memories that are crucial components in the makings of our lives, this paper seeks to investigate the processes of (re)remembering childhood worlds and the importance of thinking in more depth about the presentness of the past. Utilizing R.D. Laing's 'archive', his autobiography Wisdom, Madness and Folly (1985), and a documentary film that appeared as part of John McGreevy's Cities project in the late 1970s, this paper seeks to explore Laing's (re)remembered childhood worlds in order to think more explicitly about the significance of these different sites and spaces – and their memories – on his ways of interpreting and making sense of the world in the present. Storying (past) lives and (past) places in such a way brings to the fore the narrative quality of memory, opening up alternative ways of thinking about how memories are produced and (re)told.